2011
DOI: 10.1371/journal.pone.0019321
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of SMILE/TMTC3 in Endoplasmic Reticulum Stress Response

Abstract: BackgroundThestate of operational tolerance has been detected sporadically in some renal transplanted patients that stopped immunosuppressive drugs, demonstrating that allograft tolerance might exist in humans. Several years ago, a study by Brouard et al. identified a molecular signature of several genes that were significantly differentially expressed in the blood of such patients compared with patients with other clinical situations. The aim of the present study is to analyze the role of one of these molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…Arrestin b2 is known to have a significantly reduced expression in monocytes during kidney graft rejection as it has been recently demonstrated in human [Zakrzewicz et al, 2011] (Table I). But most importantly, the network includes the protein XBP-1 already reported by Racapé et al [2011] to be up-regulated in response to SMILE down-regulation, reinforcing these previous findings (Table I). In competition with the binding of Nephrin to the podocin, Arrestin b2 mediates Nephrin endocythosis and therefore its functioning reduction [Quack et al, 2006].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Arrestin b2 is known to have a significantly reduced expression in monocytes during kidney graft rejection as it has been recently demonstrated in human [Zakrzewicz et al, 2011] (Table I). But most importantly, the network includes the protein XBP-1 already reported by Racapé et al [2011] to be up-regulated in response to SMILE down-regulation, reinforcing these previous findings (Table I). In competition with the binding of Nephrin to the podocin, Arrestin b2 mediates Nephrin endocythosis and therefore its functioning reduction [Quack et al, 2006].…”
Section: Discussionsupporting
confidence: 87%
“…1). Using this method, we confirmed that indirect neighbors of TMTC3 are related to ER functioning and stress response genes (CANR, CALX, PDIA4, PDIA2, and ERP27) due to TMTC3 interaction with PDIA3 [Racapé et al, 2011]. The resulting map is shown in Figure 2.…”
Section: Smile Silencing In Hela Cellsmentioning
confidence: 54%
See 2 more Smart Citations
“…Proteasome inhibition by bortezomib leads to endoplasmic reticular (ER) stress and induces the pro-apoptotic unfolded protein response. Bortezomib has been shown to induce ER stress via protein overload in vitro in SMILE/ TMTC3 silenced HeLa cells and also increases transcript expression of a stress response protein, XBP-1, in HeLa cells and keratinocytes [34]. Other molecular mechanisms of bortezomib-induced sensitization to apoptosis include the generation of reactive oxygen species (ROS) and the induction of JUN N-terminal kinase [14].…”
Section: Role Of Proteasome Inhibition In Tumor Cell Death Sensitizationmentioning
confidence: 99%